ENGINEERING AND ORGANIZATIONAL PROVISION OF SAFETY TRAFFIC ON HIGHWAYS IN POLAND - I. I. Leonovich; S. V. Bogdanovich; I. V. Nestorovich (Наука и техника)
Provision of safety traffic on the highways in Poland is ensured by using signs of changing information, point light-reflecting elements and various means of regulation and control of motion speed. In addition to technical means some organizational measures are also realized in the country and they are executed under control of the State Council of Safety Traffic. The paper contains statistics about accidents for the period of2004-2006.